The Battle of the Minds in the Case of Multiple Personality Disorder in Michael Lander’s Peacock - Christy M. Uktolseya; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2014)
This paper deals with the battle of the minds in the case of John’s Multiple Personality Disorder in the movie Peacock. Through the battle of the minds between John and his alter personality Emma, I want to find out the cause, the process, and the result of the battle. To analyze the battle of the minds, I am using the theory of Multiple Personality Disorder. In my analysis, I find out that the battle of the minds is caused by the existance of the alter, the resolutions of the host, and the interference of the alter. It takes place with the attack of the alter and the defense of the host, and the result of the battle is the victory of the alter